Interaction effect of response medium and working memory capacity on creative idea generation - Hao, Ning; Yuan, Huan; Cheng, Rui; Wang, Qing; Runco, Mark A. (Frontiers in Psychology, 2015)
This study aimed to examine the interaction effect of response medium (i.e., write down ideas and orally report ideas) and working memory capacity (WMC) on creative idea generation. Participants (N = 90) with higher or lower WMC were asked to solve Alternative Uses Task (AUT) problems in the condition of writing down or speaking out ideas. The results showed that fluency of AUT performance was higher in the writing than in the speaking condition. Additionally, participants with higher WMC performed better on AUT fluency than those with lower WMC in the writing condition, while they showed no difference in the speaking condition. Moreover, level of cognitive demand fully mediated the effect of response medium on AUT fluency. Theoretically, these findings indicated the importance of WMC in creative idea generation, which supported the controlled-attention theory of creativity. Practical implications and future directions were discussed.